(3Pjd OjhGf GdVYaGAs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s; (3GHf YSGcQ , GdbGSe Hf Ydj Hf GdMSf Hf gHI Gddg, CHh eMeO , HgGA GdOjf,J (B600 (3g` s
(3ChdgG (B:s
(3gPG Pjd Ydi cJGHi (B" (3OjhGf GdVYaGA EdJbWJg ef YOI JhGdja , hgPG TF dGSHjd Edi ESJjYGHg , hEfeG gh HMSH eG YQaJ , Ch GWdYJ Ydjg s
(3BNQgG (B:s
(3hgPG BNQ GdPjd GdeHGQc hGdMeO ddg hMOg hdG Mhd hdGbhI EdG HGddg GdYdi GdYXje s
(3Vef eLehY , JQJjHgG (B: (3ef U (B227 - (3U(B239s
(3eQJH Ydi GdMQhas
(3Ydbg CMO JdGejP GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B106s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B68 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs